Jumlah Kepala Sekolah dan Guru Menurut Kelompok Umur Provinsi DKI Jakarta, Jawa Barat, Jawa Timur, Jawa Tengah Tahun 2023/2024 - Adrian Rovino Wibowo; Bayu Satrio; Khalil Akbar; Rifki Firgiawan (CV. Multi Kreasi Media, 2024)
Apart from that, this journal also explores the number of school principals and teachers in Indonesia divided into four provinces: DKI Jakarta, West Java, Central Java and East Java based on age groups. By carrying out a try out analysis using the calculation of the average, median number of school principals and teachers in all age groups. To emphasize the results, data visualization trials were carried out using histograms, frequency polygons, and ogives as colored distribution to show the number of teaching staff in the future. In this way, it is hoped that it can provide an age profile of teaching staff in the.